IMAJINER RUANG KEPALA DALAM REKAMAN GAMELAN AGÊNG DENGAN TEKNIK STEREOFONIK - Santosa, Iwan Budi (Institut Seni Indoensia Surakarta, 2020)
ABSTRACT The presentation of Javanese gamelan cannot always be present in the midst of our busy lives. In order to present musical karawitan whenever needed by the audience, it requires the recording of Javanese gamelan that can represent the original sound. Javanese people generally realize that the presentation of Javanese gamelan will be better if it is presented in pendapa. To find musical recordings as a performance in pendapa, it needs to consider the recording equipment used as well as recording techniques so that the sound will be obtained in accordance to the original sound and can bring the soul or spirit of Javanese gamelan. In order to get the gamelan recording in accordance to the original sound and to present the soul or spirit of the gamelan, the recording equipment used must adjust to the sound characteristics of the gamelan instruments and the recording uses stereophonic techniques. Stereophonics is a recording technique that is done in order to produce sounds in according to the original sound where the listeners feel to see a live performance. Keywords: Javanese Gamelan, recording, stereophonic. AbastrakPenyajian gamelan Jawa tidak selalu bisa hadir di tengah kesibukan kita. Untuk menyajikan musik karawitan setiap kali dibutuhkan oleh penikmatnya, diperlukan rekaman gamelan Jawa yang dapat merepresentasikan suara aslinya. Masyarakat Jawa umumnya menyadari bahwa penyajian gamelan jawa akan lebih baik jika disajikan dalam pendapa. Untuk mengetahui rekaman musik sebagai sebuah pertunjukan dalam pendapa perlu memperhatikan alat perekam yang digunakan serta teknik perekamannya agar didapat suara yang sesuai dengan suara aslinya dan dapat memunculkan jiwa atau ruh gamelan Jawa. Untuk mendapatkan rekaman gamelan yang sesuai dengan suara aslinya dan menghadirkan jiwa atau ruh dari gamelan tersebut, alat perekam yang digunakan harus menyesuaikan dengan karakteristik bunyi dari alat musik gamelan tersebut dan perekamannya menggunakan teknik stereofonik. Stereophonics adalah teknik perekaman yang dilakukan untuk menghasilkan suara yang sesuai dengan suara aslinya dimana pendengar merasakan secara langsung pertunjukannya. Kata kunci: Gamelan Jawa, rekaman, stereofonik.